Explaining the Model of the Antecedents of Entrepreneurship intents: A Sociological Approach - FARAJALLAH RAHIMI; Sara Mohammadi; sepideh javadnia (توسعه اجتماعی, 2023)
Entrepreneurship is a process that plays a vital role in the continuation of national growth and development and even the global economy. The improvement of entrepreneurship creates new economic opportunities and businesses in society. Today, accumulating evidence suggests that gender plays an important role in entrepreneurship. The participation of women as a half of the population has significant impact on the expansion of social and economic activities. However, in recent years, the gender gap in entrepreneurship is one of the most important discrimination that women have been facing in the labor market. The present study was performed to assess the Explaining the Model of the Antecedents of Entrepreneurship intents: A Sociological Approach. Research in terms of purpose, type of applied research, and in terms of data collection method, is considered as descriptive (non-experimental) research. The subjects in this study were those who participated in seminars, startup events and ideas in Khuzestan province, southwest of Iran. The sampling method was a simple random sampling technique and data were collected using questionnaire. A total of 384 questionnaires were administered to the participants. A positive and significant relationship was observed between hostile gender sexism and gender stereotypes. In contrast, no significant relationship was found between benevolent sexism and gender stereotypes. No significant relationship was noted between hostile sexism and entrepreneurial intention. On the other hand, a positive and significant relationship was observed between benevolent sexism and entrepreneurial intention. Gender stereotypes play a mediating role in the relationship between hostile and benevolent sexism and entrepreneurial intention. Finally, research findings indicate that the process of socialization, educational status and family ideology can have a significant effect on women’s activity in busuness areas.